The Golden head: Effect of size and season of catch on physicochemical properties of cod heads - Elísa Viðarsdóttir 1991- (2018)
Fishing of cod began many years ago in Iceland and has since then been one of the most important fish species for the Icelandic fish industry. The utilization of cod is good compared to other fish species. However, the utilization of the fish head, especially in trawlers, has not been good because the majority of the trawlers do not have enough space or equipment to bring the heads to land. The overall aim of the project was to promote further development of valuable products from cod heads (Gadus morhua) to compensate for the market instability that has been observed recently for the dried cod heads. The first step towards further development and value creation was to create an important knowledge database of physicochemical properties of the various parts of the head, i.e. the cheeks, tongue, eyes, brain and gills. When creating such a database it is necessary to take into the account the biological variability of the fish, season of catch and the size of the fish. When the characteristics of the head have been mapped thoroughly, the road towards further product development and value creation will be more accurate and profitable. In this study, samples were taken in May and November 2017. The eyes, brain, gills, cheeks and tongue were examined separately with regards to size of the fish and season of catch. Results showed for example that the fat content in the brain was significant higher than the fat content in the other four parts. The highest fat content was observed in the 6-7 kg heads from fish caught in November, or 5%, while the fat content in the other parts (eyes, gills, brain, cheeks and tongue) varied from 0.2-0.9%. The results from this study showed that the water content held in hand with protein and fat content in the varius parts. If the water content was high, the protein and fat content was low and vice versa. The ash content in the gills was way higher than in the other parts, that could be due to the composition of the gills. The Omega-6/omega-3 balance was high in all the parts. this high ...